Production of Recombinant N Protein of Infectious Bronchitis Virus Using the Baculovirus Expression System and Its Assessment as a Diagnostic Antigen - Yilmaz, Huseyin; Faburay, Bonto; Turan, Nuri; Cotton-Caballero, Maira; Cetinkaya, Burhan; Gurel, Aydin; Richt, Juergen A. (Springer, 2019)
The avian coronavirus-infectious bronchitis virus (AvCoV-IBV) is recognized as an important avian pathogen, and new viral variants are a continuous threat to the poultry industry worldwide. Sensitive diagnostics and efficacious vaccines are necessary to combat IBV infections in chickens. The aim of this study was to produce recombinant N protein of IBV in the baculovirus system to use in ELISA diagnostic tests in order to enable the assessment of the sero-prevalence and risk of IBV infections in chickens in Turkey. For this, the gene encoding the N protein of the Beaudette strain of IBV was expressed using a recombinant baculovirus expression system. The recombinant N protein was purified using Ni-NTA affinity chromatography. An estimated 50-kDa recombinant protein corresponding to the expected molecular weight of IBV N including the 6xHis tag was detected using an anti-His monoclonal antibody. Specific immunoreactivity of the recombinant protein was confirmed by Western blot using antiserum obtained from vaccinated and naturally infected chicken from Turkey as well as using a monoclonal antibody raised against the N protein of the IBV Massachusetts strain. The results obtained with the in-house ELISA had high agreement with a commercial ELISA. Immunoreactivity analysis using antisera in Western blotting and the in-house ELISA suggests that the recombinant IBV N protein could be broadly cross-reactive with antisera produced against different IBV strains. We conclude that the recombinant baculovirus expressed IBV N protein could serve as a useful diagnostic antigen for detection of IBV infections in chickens by ELISA.
Keywords: Infectious bronchitis virus; Baculovirus; Expression; Recombinant; N protein